Analysis of Demodex infection of facial hair follicles and skin biophysical parameters in different subtypes of rosacea - Wei LI; Jingyao LIANG; Weiyu LIU; Xiaodong LI; Yichuan GAN; Qian LI; Shanshan OU; Yumei LIU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To analyze the Demodex infection in facial hair follicles and the changes in skin biophysical properties in different subtypes of rosacea. Methods A total of 32 patients with erythematotelangiectatic rosacea (ETR) and 40 cases with papulopustular rosacea (PPR) were enrolled in this study. A reflectance confocal microscopy (RCM) was used to examine Demodex folliculorum infection on the forehead and the cheeks. The rate of Demodex folliculorum infection, the number of infected hair follicles, total Demodex count per scanned area, the number of Demodex per hair follicle and number of Demodex per infected hair follicle were analyzed. A non-invasive skin physiological device was used to measure the stratum corneum hydration, TEWL, sebum, melanin and erythema indices, and skin elasticity. Skin biophysical parameters and Demodex infection were compared between ETR and PPR. Results In subjects aged >31 years and disease duration of >3 years, the rate of Demodex infection, the number of infected hair follicles, total Demodex count per scanned area, the number of Demodex per hair follicle and number of Demodex per infected hair follicle were higher in PPR patients than in ETR patients (P<0.05). However, these parameters did not differ significantly between ETR and PPR in individuals aged over 31 years and disease duration of ≤3 years, and individuals aged ≤31 years (P>0.05). Moreover, skin biophysical properties, including melanin and erythema indices, sebum and stratum corneum hydration levels, elasticity, and TEWL, were comparable in ETR and PPR patients (P>0.05). Conclusion Demodex folliculorum infection, but not skin biophysical properties, is influenced by patients' age, disease duration and the subtypes of rosea.